Performance Analysis of Disk Scheduling Algorithms - Mallikarjuna, C; Chitti Babu, P (International Journal of Computer Sciences and Engineering, 2025)
This paper aims to make performance analysis of various disk scheduling algorithms based on various factors. In these disks scheduling algorithms we consider First Come First Serve (FCFS), Shortest Seek Time First (SSTF), Scan, Look, C-Scan, and C-Look Scheduling Algorithms. Based on head movements of various disk scheduling algorithms we made performance analysis. These head movements are calculated for different disk scheduling algorithms while serving disk requests. Here we consider the performance factors such as access time, Disk throughput, Disk Utilization etc.